The Concept of Dzari'ah on Preventing Transmission of Covid-19 (PSBB and PPKM Government Policy Analysis Study) - Miskari Miskari (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2022)
This study will comprehensively discuss the spread of Covid-19, which until now continues and continues to grow and even gives rise to new variants. Therefore, several countries have decided on several policies to stop the spread of the Coronavirus. Not Indonesia, one of the countries affected by COVID-19, has also issued several important guidelines. The government is the party that implements and takes action in giving PSBB and PPKM policies. The policy regulates various aspects of people's lives, ranging from tightly closed education aspects to learning from home (online), aspects of work, implementation of work from home (WFH), and aspects of worship (adjusting the distance of prayer), to closing places of worship to the public. . This research method uses a literature study that uses documentation techniques in finding data. The approach used is normative by analyzing government policies using Dzari'ah theory. The results of this study indicate that the guidelines taken by the government regarding PSBB and PPKM follow what was taught by the Prophet Muhammad. This policy was implemented and followed by the companions of the Prophet as well. This policy aims to maintain the health and strength of Muslims spiritually and physically. Kajian ini akan membahas secara komprehensip tentang penyebaran Covid-19 yang hingga saat ini terus berlanjut dan terus berkembang bahkan memunculkan varian-varian baru. Oleh karena itu, beberapa negara telah memutuskan beberapa kebijakan untuk menghentikan penyebaran virus corona. Bukan Indonesia, sebagai salah satu negara yang terkena covid 19, juga mengeluarkan beberapa kebijakan penting. Pemerintah sebagai pihak yang melaksanakan dan mengambil tindakan mengeluarkan kebijakan PSBB dan PPKM. Kebijakan tersebut mengatur berbagai aspek kehidupan masyarakat, mulai dari aspek pendidikan yang tertutup rapat, hingga pembelajaran dari rumah (online), aspek pekerjaan, pelaksanaan work from home (WFH), dan aspek ibadah (penyesuaian jarak ibadah), hingga menutup tempat ibadah untuk umum. Metode penelitian ini menggunakan studi literatur yang mengunakan teknik dokumentasi dalam mencari data. Pendekatan yang digunakan adalah normatif yakni dengan menganalisis kebijakan pemerintah mengunakan teori Dzari'ah. Hasil penelitian ini menunjukkan bahwa kebijakan yang diambil pemerintah mengenai PSBB dan PPKM mengikuti apa yang diajarkan oleh Rasulullah SAW. Kebijakan ini dilaksanakan dan diikuti oleh para sahabat Nabi juga. Tujuan dari kebijakan ini adalah untuk menjaga kesehatan dan kekuatan ummat Islam secara rohani dan jasmani.